2013
DOI: 10.1111/add.12256
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐related biases in selective attention and action tendency make distinct contributions to dysregulated drinking behaviour

Abstract: Biases in selective attention and action tendency appear to be distinct mechanisms that contribute independently to difficulty regulating alcohol consumption. Treatment components that could be combined to target both mechanisms could enhance treatment outcomes for alcohol-use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 37 publications
3
29
3
Order By: Relevance
“…Therefore, a main effect of approach bias may be more likely found in samples with low inhibitory control (e.g., overweight or obese individuals) than in the present sample (which had on average good inhibitory control). Taken together, the results confirm that attentional and approach biases are two distinctive types of cognitive bias, which is consistent with previous research in the alcohol domain (Sharbanee et al, 2013). Although both attentional and approach biases are components of automatic processing, the current findings suggest that approach bias may be more pertinent to understanding the association between food cues and eating behaviour.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, a main effect of approach bias may be more likely found in samples with low inhibitory control (e.g., overweight or obese individuals) than in the present sample (which had on average good inhibitory control). Taken together, the results confirm that attentional and approach biases are two distinctive types of cognitive bias, which is consistent with previous research in the alcohol domain (Sharbanee et al, 2013). Although both attentional and approach biases are components of automatic processing, the current findings suggest that approach bias may be more pertinent to understanding the association between food cues and eating behaviour.…”
Section: Discussionsupporting
confidence: 91%
“…One possible explanation for these contradictory findings is that attentional and approach biases behave differently, as has been evidenced by research in the alcohol domain. Specifically, Sharbanee, Stritzke, Wiers, and MacLeod (2013) demonstrated that these two cognitive biases are distinct mechanisms that can make independent contributions to consumption. Another potential explanation for the overall mixed evidence is that the previous research has not taken into account the role of controlled processing in consumption.…”
mentioning
confidence: 99%
“…Our results question predictions from 2-systems models for a direct relationship between motivational biases and inhibitory control performance (Field and Cox, 2008;Strack and Deutsch, 2004), and rather suggest that i) modifications in the ability to withhold responses to incentive-motivational stimuli only manifest in situations of extreme biases and/or abnormally low inhibition (Dawe et al, 2004) ii) ABM might modify a type of bias that do not directly influence control capacities (e.g. attentional vs. approach bias; Sharbanee et al, 2013) or iii) that decision-related "cognitive" impulsivity which would interact with AB, should be distinguished from the "motor" impulsivity measured in our study (de Wit and Richards, 2004;Olmstead, 2006;Reynolds et al, 2006). Our negative results however call for emphasizing that automatic and controlled systems in dual process models might be independent from each other.…”
Section: Discussioncontrasting
confidence: 85%
“…This suggests that alcohol consumption was driven more by the action tendency than by selective attention immediately post-training, whereas both processes may make a more equal contribution to drinking behaviour in other situations (e.g., [9]). …”
Section: Discussionmentioning
confidence: 99%